Analisis Pengelolaan Manajemen Sumber Daya Manusia (SDM) dalam Upaya Meningkatkan Kinerja SPPG MBG di Kabupaten Tangerang (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aims to analyze human resource management (HRM) practices, identify factors influencing employee performance, and evaluate performance improvement efforts at SPPG MBG in Tangerang Regency. The study employed a qualitative approach using a case study design. The participants consisted of eight informants, including managers, administrative staff, supervisors, and operational employees, who were selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation. The data analysis process involved data reduction, data display, and conclusion drawing. The findings indicate that HRM practices have been implemented reasonably well through task allocation, work supervision, internal coordination, and employee development. However, several challenges remain, including the absence of a structured training program, a performance evaluation system that lacks objectivity, and the lack of formal recognition for high-performing employees. Factors influencing employee performance include work motivation, leadership, work environment, internal communication, and teamwork. Efforts to enhance performance have been carried out through regular briefings, direct supervision, and motivational support provided by management. This study was conducted in only one SPPG MBG unit in Tangerang Regency with a limited number of informants; therefore, the findings cannot be broadly generalized to other organizations or regions with different characteristics. The study recommends strengthening HRM systems through more systematic, measurable, and sustainable approaches to improve employee performance and organizational effectiveness.